Monopolar teres major muscle transposition to improve shoulder abduction and flexion in children with sequelae of obstetric brachial plexus palsy - Bahm, Jörg; Ocampo-Pavez, Claudia (Journal of Brachial Plexus and Peripheral Nerve Injury, 2009)
We present a new surgical technique for a pedicled teres major muscle transfer to improve shoulder abduction and flexion in children with sequelae of obstetric brachial plexus palsy.In addition, we provide the clinical outcome in the first 17 operated children.